Recovering multiplexing loss and improving reliability in cooperative half-duplex relay networks - Harya Wicaksana (2012)
To meet the rapid growth of wireless applications and multimedia services, the development of wireless communications that is able to provide higher data rates and more reliable communications while maintaining satisfactory quality of service is required. Multiple-input multiple-output (MIMO) system has shown tremendous potential to be an excellent approach for solving this problem by providing multiplexing and spatial diversity gains without requiring additional radio resources, such as bandwidth and power. However, the size and complexity limitations of wireless mobile devices mean that MIMO systems may possibly be unfeasible, especially for the uplink. For this reason, cooperative communications has been proposed and its potential benefits have attracted much research attention in the past few years. The idea of this technique is to utilize the broadcast nature of wireless signals by exploiting the fact that a signal intended for a particular destination node can be overheard at neighboring nodes, and thus these nodes can help each other to create a virtual MIMO system. Spectral efficiency (multiplexing gain) and reliability (diversity gain) are the two most important features of cooperative communication protocols. Many cooperative communication protocols are able to achieve full spatial diversity gain, but fail to exploit the multiplexing gain. It is observed in many cases that the multiplexing gain is reduced to one-half due to the half-duplex constraint of the relay. Thus, in this thesis, we investigate cooperative communications protocols that are able to enhance this spectral efficiency (recover multiplexing loss) and improve the corresponding reliability in wireless networks. Specifically, we first analyze the performance of amplify-and-forward (AF) two-path, also known as successive half-duplex, relaying protocol where two-relays are utilized to alternate between transmission and reception modes. This protocol is very interesting, but less studied in the literature due to inter-relay interference inherent in this protocol.